Simulations of thermal softening in large strain thermoplasticity - WCISŁO, Balbina (Engineering Transactions, 2016)
This paper deals with numerical simulations of the thermoplastic behaviour of isotropic materials undergoing large deformations. The attention is focused on the constitutive modelling of thermal softening understood here as a reduction of the plastic strength with increasing temperature. Different concepts of thermal softening embedded in the plasticity function are considered, in particular, the reduction of the total yield strength, its initial value or the hardening part. Moreover, apart from linear dependencies between temperature and the yield strength, the formulation involving function arc tangent is proposed. The analysed models are numerically tested in the finite element environment AceFEM using subroutines generated with the AceGen code generator. In particular, shear banding in an elongated rectangular plate with imperfection in plain strain conditions is investigated.